Assessment of the Effect of Remittance on the Economic Growth of Nepal: A Time Series Analysis - Acharya, Rupesh; Neupane, Deepak (Journal of Interdisciplinary Studies, 2025)
This study examines the impact of remittance on the economic growth of Nepal employing time series data. The analysis has incorporated the macroeconomic variables such as GDP, Remittance (REM), Balance of Payments (BOP), Private Consumption (PCO), and Private Investment (PIN), using 48 years observations. Unit root tests indicated that the variables are integrated at mixed levels of I (0) and I (1), justifying the use of ARDL model. A structural break in 2010 was incorporated using a dummy variable. The long-run results indicated a significant negative relationship between remittance and GDP, where a percentage increase in remittance reduces GDP by 0.155 percent. BOP, PCO, and PIN exhibited positive but statistically insignificant long-run effects. In the short run, remittance has a significant negative effect in the current year but significant positive impacts in its first and second lags. The error correction term is -0.5972, suggesting that nearly 60 percent of the short-run disequilibrium adjusts back to long-run equilibrium annually. A significant positive time trend and structural break influence were also observed through the analysis of the data. The model was approved through all the major diagnostic and stability tests, reflecting the reliable results. Findings suggest that while remittance may support short-term consumption, they do not have positive contribution in the long-term economic growth.